2018
DOI: 10.1021/acschembio.7b00980
|View full text |Cite
|
Sign up to set email alerts
|

Dual Allosteric Inhibition of SHP2 Phosphatase

Abstract: SHP2 is a cytoplasmic protein tyrosine phosphatase encoded by the PTPN11 gene and is involved in cell proliferation, differentiation, and survival. Recently, we reported an allosteric mechanism of inhibition that stabilizes the auto-inhibited conformation of SHP2. SHP099 (1) was identified and characterized as a moderately potent, orally bioavailable, allosteric small molecule inhibitor, which binds to a tunnel-like pocket formed by the confluence of three domains of SHP2. In this report, we describe further s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 41 publications
1
101
0
Order By: Relevance
“…The above referenced allosteric SHP2 inhibitors such as SHP099, SHP394, and RMC-4550 bind to the tunnel-like pocket formed by the confluence of three domains of SHP2 (site 1 inhibitor) and stabilize the closed auto-inhibited state of SHP2. We also reported a series of site 2 allosteric inhibitors such as SHP244 that bind to a distinct latch-like allosteric site in a cleft at the interface of the N-terminal SH2 and PTP domains [29]. We also demonstrated that site 1 and site 2 inhibitors can simultaneously bind to SHP2 and cooperatively stabilize the closed inactive conformation of SHP2 [29].…”
Section: Rapid Feedback Activation Of Fgfr Causes Resistance To Shp2 mentioning
confidence: 77%
“…The above referenced allosteric SHP2 inhibitors such as SHP099, SHP394, and RMC-4550 bind to the tunnel-like pocket formed by the confluence of three domains of SHP2 (site 1 inhibitor) and stabilize the closed auto-inhibited state of SHP2. We also reported a series of site 2 allosteric inhibitors such as SHP244 that bind to a distinct latch-like allosteric site in a cleft at the interface of the N-terminal SH2 and PTP domains [29]. We also demonstrated that site 1 and site 2 inhibitors can simultaneously bind to SHP2 and cooperatively stabilize the closed inactive conformation of SHP2 [29].…”
Section: Rapid Feedback Activation Of Fgfr Causes Resistance To Shp2 mentioning
confidence: 77%
“…Most recently, the development of allosteric SHP-2 inhibitors has been employed to circumvent these problems using computer-aided drug designs to discover SHP-2 inhibitors [11,19,20,56]. Recently, the medical chemistry of the SHP-2 inhibitor SHP099 has been reported [20].…”
Section: Shp-2mentioning
confidence: 99%
“…The in silico mutant structure was used as the reference structure during the 3-50 ns MD simulations. It was worth noting that the region Gln 255-Arg 265 was an allosteric pocket that affected the opening and closing of the SHP2 switch, 52,53 which was the focus in this study. The effects of translation and rotation were eliminated during the simulation progress.…”
Section: Shp2-wt System and Shp2-e76k Systemmentioning
confidence: 99%
“…These results showed that the mutant protein had higher flexibility than the wild-type protein. It was worth noting that the region Gln 255-Arg 265 was an allosteric pocket that affected the opening and closing of the SHP2 switch, 52,53 which was the focus in this study. Moreover, the RMSF values of the loop region Ile 310-Asn 320 were 0.41 nm and 0.35 nm in the SHP2-E76K system and the SHP2-WT system, respectively.…”
Section: Shp2-wt System and Shp2-e76k Systemmentioning
confidence: 99%